On Frobenius groups with noninvariant factor SL 2(3) - Kozulin, S. N.; Senashov, V. I.; Shunkov, V. P. (Ukrains’kyi Matematychnyi Zhurnal, 2006)
We obtain a criterion for the unsimplicity of an infinite group containing the infinite class of the Frobenius groups $L_g = \langle a, g^{-1} a g\rangle$ with complement $SL_2 ( 3 )$.